From the Anthroponymy of Cetain Settlements on the Pešter Plateau on Old Islamic Tombstones (Nišans) from XVIII and XIX Century - Novakov, Dragana; Škrijelj, Redžep (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Based on the collected material from Pešter, the paper analyzes personal names and nicknames extracted from the oldest epitaphs. This research covers sources dating from the 18th and 19th centuries. On this occasion, we will not present the entire anthroponymic layer of Pešter, as many of the monuments are badly damaged (broken, sunk or covered with moss). The general part of the paper includes a concise overview of the history of Pešter, the analysis of its former and present territorial span, as well as an overview of the origin of some families. The second part of the work is based on the field research and analysis of the anthroponyms read. Much of the rich epigraphic material on Pešter has not been scientifically researched to date, which is the case with the inscriptions on the grave notes that form the subject of this paper.